A case-control study of the lipid profile of women with breast cancer - Piasecka, Katarzyna; Stanisławek, Andrzej; Stasiak, Elżbieta; Irzmańska-Hudziak, Anna; Kociuba-Adamczuk, Katarzyna (Journal of Education, Health and Sport, 2020)
<p class="MsoNormal" style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" align="justify">Purpose: Neoplastic diseases remain the second most common cause of death, behind cardiovascular diseases, and breast cancer is the leading cause of death among women worldwide. Increased incidence of neoplastic diseases is also known to be accompanied by lipid metabolism disorders. <p class="MsoNormal" style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" align="justify">Method: Blood samples for lipid profile testing were taken from the two studied groups, which comprised 110 women with breast cancer and 70 healthy women. Lipid profile testing was conducted on venous blood samples collected among both groups of women on an empty stomach. Statistical analyses were performed using the IBM SPSS Statistics 20 software package. <p class="MsoNormal" style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" align="justify">Results: A statistically significant (p<0.05) majority of women with breast cancer had abnormal TC results (67.3%). A statistically significant (p<0.05) majority of control group women (90.0%) had normal HDL-C results. More women with breast cancer (87.3%) had abnormal LDL-C results than healthy women (62.9%), which represented a statistically significant difference (p<0.05). <p class="MsoNormal" style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" align="justify">Conclussions: Abnormal lipid profile significantly impacts breast cancer incidence. At the same time it is under influence of abnormal eating habits and low physical activity. Community and oncology nurses, having considerable knowledge about health and lifestyle of their patients, should be more involved in basic education to decrease cancer risk, especially by women with alarming LDL-C level.